Regional and international variables and their impact on the Qatari-Saudi relations crisis (قضايا سياسية, 2022)
The Research deals with the issue of the crisis that afflicted the Qatari-Saudi relations and the effects of the regional and international variables on it. The research believes that the crisis has multiple causes, the most prominent of which is the difference in political orientations between the leaderships of the two countries between the State of Qatar, which aspires to play a regional role outside the Saudi mantle, and between the vision of Saudi Arabia, which historically finds itself the elder brother of countries The Gulf system, which has historically been accustomed to represent its policies, the road map for the GCC states as a whole. The research starts first from the historical accumulation of Qatari-Saudi relations, then deals with the most prominent causes of the crisis, then turns to the study of regional variables as well as international variables active and influencing the crisis, based on our awareness that these variables played a major role in escalating the severity of the crisis until it reached the severance of diplomatic relations And the high level of disagreement. For the purpose of dealing with the research, the structure was distributed among two topics. The first topic dealt with the history of Saudi-Qatari relations and the role of the internal variable in the crisis. While the second topic deals with the role of international and regional variables. The research came out with the result that the international variable has become more influential in the crisis, and that whenever the United States wants it to end, it will pressure the two parties to work to end it, and this does not mean that the causes of the crisis are all external, inasmuch as the external variable has an important role in directing it in a manner commensurate with its nature Regional and international developments taking place.